A new nation : (McGraw-Hill School Division, 2000)
A new nation : Advantures in time and place includes: American and our environment; Culture west and east; Contact and exploration; The 13 english colonies; The fight for independence ; Building the United states; Westward expansion and change; The United State, past and present.